India’s Cold Start Doctrine and Pakistan’s Counter Strategy - Syed Ali Raza Shah; Muhammad Zohaib (ASIAN Journal of International Peace & Security (AJIPS), 2021)
This paper highlights the objectives and Modus Operandi of India’s Cold Start Doctrine, as well as Pakistan’s counter-strategies to protect its national security from Indian attack. The bilateral relations of both states became distrustful, conflicting, and hostile, as India and Pakistan gained independence from British rule. India-Pakistan relations are complicated because the century’s most active fault line runs between them. In order to become a major power in South Asia, India is focusing on developing Pakistan-centric war doctrines, as Pakistan is the only country in the region with military parity. The Cold Start Doctrine is one such attempt as it aims to achieve military and political objectives through shallow penetration into strategically important positions. It is a limited war doctrine that operates below the nuclear threshold. Pakistan, on the other hand, is strengthening its conventional edge by developing counter-strategies and doctrines as its national security paradigm evolves. Pakistan successfully developed a conventional advantage and substantial parity with India, and its tactical nuclear weapons provide a deterrence against any conventional challenge from India.